PENDIDIKAN KARAKTER DI SEKOLAH MENANAMKAN NILAI NILAI LUHUR SEJAK DINI - Agus Faisal Asyha; Novalinda Mohamad; Sulvia Fery Hanry Tondowala; Abubakar; Sepryanus Rano Putra; Aat Ruchiat Nugraha (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Character education in schools is a fundamental step in shaping young people who have noble values such as honesty, responsibility, discipline and tolerance. This article discusses the importance of character education as an integral part of the national education system, as well as various implementation strategies that can be applied in the school environment. Cultivating noble values from an early age helps students build a strong personality, good ethics and social skills that support community life. The article also reviews the challenges in implementing character education in schools, including the role of teachers, the curriculum and collaboration with parents. With an integrated approach and support from all parties, character education has the potential to create a generation that is not only intellectually smart, but also superior in morals and behavior.